RESISTANCE TO CLIMATE IMPACT STRUCTURES FACADE THERMAL INSULATION FINISHING PLASTER - and (Municipal economy of cities (Technical science), 2013)
The article present the result of experimental research of resistance to climatic influences design of facade insulation finishing plaster and determine the actual thermal performance team system.